Protocol of Life Cycle Cost (LCC) data input requirements process of road pavement types. - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2017)
A protocol of LCC data input requirements process has been developed, evaluated, validated and tested with a group of people that have knowledge, skills and experience in LCC analysis of road pavement. The protocol provides procedures that can facilitate the clients, researchers and LCC practitioners in performing the task to identify, access, update and check the reliability of data before the data can used as inputs to estimate the total cost of road pavement and to compare the most cost-effective between the renewal and maintenance of existing two different types of road pavement (i.e. flexible and rigid pavements). The developed protocol comprises of three components: